Perancangan Dan Pembuatan Sistem Informasi Akuntansi Pada Toko It Solution - Arina Juwita; Jesica Jesica (ConCEPt - Conference on Community Engagement Project, 2021)
The IT Solution store, which has been operating for a long time, does not yet have an adequate accounting recording system. Employees only record cash receipts and disbursements transactions every day. Recordings that have not yet produced financial reports can cause business owners to find it difficult to assess their business performance. To solve this problem, the authors devise an accounting information system that can produce financial reports in the form of balance reports, profit and loss, purchases, sales of merchandise and remaining stock with Microsoft Access software based on data obtained from observations and interviews. The system designed is still very simple, therefore for further researchers, it can add system functions to produce cash flow reports, reports of changes in capital or other reports.